Changes In The Function Of Manimbong Music In The Rambu Tuka' Ceremony Of The Toraja People (Jurnal Seni Musik, 2022)
Talking about traditional music, it is important to discuss the religious beliefs of the people around the music. This also applies to the Toraja tribe, which is located in the mountainous region of the southern island of Sulawesi. One of the arts that exist within the Toraja environment is Manimbong. Manimbong is a Torajan art form that combines two arts, music and dance, performed by a group of men at the Rambu Tuka' ceremony. This art is known as the art of Aluk Todolo (Toraja tribal religion). The introduction of Christianity in Toraja society has also affected some Toraja cultures. This research aims to see the changes in function that occur in Manimbong. In analyzing this research to see changes in the function of Manimbong using descriptive qualitative research methods. Primary and secondary data were obtained using observation, interview, and document study data collection techniques. Credibility criteria as a basis for conducting data validation techniques and data triangulation are in the standard of degrees of trust. The conclusion of this research is that Manimbong is not an art owned by Aluk Todolo or Christian, but belongs to all Toraja people. In addition, in the process of changing its function, Manimbong changes according to the context of several things, such as changes in the meaning of the poem of Manimbong itself in both Christianity and Aluk Todolo, as well as in the context in which Manimbong is performed or staged.